2015
DOI: 10.1016/j.quaint.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Holocene climate change and prehistoric settlement in the lower Danube valley

Abstract: An analysis of the summed probability distributions of 293 radiocarbon dates from Late Glacial to mid-Holocene sites in the Danubian Iron Gates highlights the existence of well-marked 14 C discontinuities at c. 9.5-9.0 ka, 8.65-8.0 ka and after 7.8 ka cal BP. These coincide with climate anomalies recorded in Greenland ice cores and palaeoclimate archives from the Danube catchment. Four possible explanations are considered: dwindling fish resources, changes in the social environment, floodinduced settlement rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
10
0
2
Order By: Relevance
“…While the record for the Mesolithic and Neolithic periods is good, thanks to the presence of famous sites that have attracted continuous scientific attention (e.g. the Danube Gorges and the site of Vinča; see recently Bonsall et al 2015; Tasić et al 2016), later periods are less well-covered. This situation is particularly unfortunate as this area lies at the crossroads of many natural communication routes connecting central Europe with the Balkan peninsula and, beyond, the Aegean and the Adriatic seas.…”
Section: Introductionmentioning
confidence: 99%
“…While the record for the Mesolithic and Neolithic periods is good, thanks to the presence of famous sites that have attracted continuous scientific attention (e.g. the Danube Gorges and the site of Vinča; see recently Bonsall et al 2015; Tasić et al 2016), later periods are less well-covered. This situation is particularly unfortunate as this area lies at the crossroads of many natural communication routes connecting central Europe with the Balkan peninsula and, beyond, the Aegean and the Adriatic seas.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks that surpass the mean value of the relative probability indicate that during that time the fluvial activity on the rivers had a greater intensity than in other time intervals. These years are indicated on the figure next to the peaks, respectively: 6200, 5300, 4100-4080, 3600, 23004100-4080, 3600, -22004100-4080, 3600, , 19004100-4080, 3600, , 1300 The fluvial units on the rivers from Siret basin which were exemplified here, supplemented by other documented reports for Romania (Howard et al, 2004;Perșoiu, 2010;Bonsall et al, 2015; lead to the conclusion that periods of alluvial sedimentation correlate well with episodes of climatic cooling, higher rainfall and enhanced river activity.…”
Section: Discussionmentioning
confidence: 56%
“…Bonsall et al . 47,48 have previously argued that this particular climatic oscillation dated between c. 6300 and 6100 cal BC might have affected significantly Late Mesolithic settlement pattern in the Danube Gorges area along the river edges and especially low-lying portions of the sites due to the increased risk of flooding, thus prompting relocation of settlements. It should be noted that to date the only evidence used to argue this scenario in the Danube Gorges area comes from the distribution of radiocarbon dates with arguable “gap” in the occupation of all sites except Lepenski Vir during this cold spell.…”
Section: Discussionmentioning
confidence: 99%
“…48 also suggested that lower lying parts of Lepenski Vir were affected by flooding, which might have removed datable material during floods, prompting people to move their dwelling structures to higher parts of the site. This scenario is unlikely on the basis of the evidence presented here for two reasons.…”
Section: Discussionmentioning
confidence: 99%